COVID-19 and The City: A Healthy City Strategy for Pandemic Challenges, from Planning to Action - Hasyim, Hamzah; Dale, Patricia (Kesmas, 2021)
COVID-19 is a respiratory disease caused by SARS-CoV-2, a new coronavirus discovered in 2019. WHO declared COVID-19 is a respiratory disease causedby SARS-CoV-2 as a pandemic that the detection level of cases changed daily, and it can track almost in real-time. This paper used a narrative literaturereview to address issues of urban quality and lack of exercise. The specific aim was to discuss the concept of a healthy city, indicate a new urban model, andadvocate for the increased use of bicycles, outdoor gym/outdoor exercise, walking to reducing pollution, and improving physical, psychological, and social fitness. A healthy city can improve residents’ health by improving conditions of life to face COVID-19 pandemics. It needs the local capacity to prevent thespread of the diseases and design public health concepts concerning the built environment and contemporary towns in a new urban model. Dialogue opportunities in public health can provide essential guidance for designers (architects and town planners), decision-makers, public health experts, and health agencies locally, promoting the actions and policies to transform the city into a healthier neighborhood and salutogenesis.